Role of Urokinase in Delayed Presentation of Deep Vein Thrombosis: Single Center Experience - Kesha Shah; Apurva Shah; Sourabh Mittal; Sunil Dixit; Anil Sharma (Indian Journal of Vascular and Endovascular Surgery)
Background: Deep vein thrombosis (DVT) is a common and potentially devastating condition that can lead to permanent disability with significant morbidity and mortality. Current management of DVT stands on three pillars (1) anticoagulant therapy (2) graduated elastic compression stockings, and (3) early ambulation. Thrombolysis proved its effective role in the prevention of long-term complications of postthrombotic syndrome and resolution of symptoms in case of acute DVT (<21 days presentation) because of its clot lysis action. This study was conducted to evaluate the role of urokinase (thrombolytic agent) in patients with delayed (>3 weeks to 3 months) presentation of DVT. Materials and Methods: We conducted a retrospective study in a tertiary-level hospital in India and included patients with delayed presentation (>3 weeks to 3 months) of DVT in the past 3 years. A total of 258 patients were included in the study and were subjected to thrombolysis by urokinase using the standard dose. Results and Conclusion: Pathologically thrombi of 15 days old or more become increasingly resistant to both anticoagulation and thrombolytic therapies but we concluded that up to 3 months of presentation of DVT when subjected to urokinase infusion gave significant positive results in terms of resolution of symptoms and prevention of complications. None of the patients was referred for venous filter due to failure of thrombolysis proving that aggressive management with thrombolysis also in delayed presentation of DVT with urokinase not only shows a noteworthy reduction in symptoms but also decreases morbidity associated with the disease in long term.